1999
DOI: 10.1007/s004020050424
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic spontaneous posterior subluxation of the sternoclavicular joint

Abstract: We report a case of atraumatic spontaneous posterior subluxation of the sternoclavicular joint in a 19-year-old woman without any known underlying pathology. There was no history of injury. The patient was treated operatively using the gracilis tendon to reinforce the anterior sternoclavicular ligament. One year later the patient is asymptomatic and has returned to her usual life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Reported methods included fixation with large cannulated screws, anterior plating, K-wire fixation, Steinmann pin fixation, external fixate, medial clavicle resection, and soft tissue procedures such as tendon grafts, facial loops, fiber wires, and synthetic ligaments. 4,6,9,16,21,24,26,32,38,45,57 A recent review showed overall a good functional outcome using different modalities of treatments in adults. 21 However, complication rate of hardware fixation has been unacceptably high, and some authors do not support their use.…”
Section: Closed Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reported methods included fixation with large cannulated screws, anterior plating, K-wire fixation, Steinmann pin fixation, external fixate, medial clavicle resection, and soft tissue procedures such as tendon grafts, facial loops, fiber wires, and synthetic ligaments. 4,6,9,16,21,24,26,32,38,45,57 A recent review showed overall a good functional outcome using different modalities of treatments in adults. 21 However, complication rate of hardware fixation has been unacceptably high, and some authors do not support their use.…”
Section: Closed Reductionmentioning
confidence: 98%
“…Atraumatic dislocations are rare; however, 3 cases of spontaneous posterior dislocation have been reported in the literature in patients with generalized laxity. 12,37,38 Clinical presentation and investigation Patients with posterior SCJ dislocations present with pain localized to the joint, palpable gap, or swelling at the medial end of clavicle. The gap is often subtle and may remain unrecognized; hence, a high index of suspicion must be maintained unless the injury is ruled out.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Possible treatment options are described in a large variety employing the fixation of the clavicle against the manubrium through a sternoclavicular plate at the anterior surface thus archieving a functional arthrodesis or a hook plate (10,11). With the aim to provide a more functional result, the stabilization of the SCJ had been widely described by sternoclavicular sutures, wires or autologous tendons in order to stabilize the destroyed parts of the SCL (12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…These luxations are caused mainly by trauma, mostly car accidents and sporting accidents [5,10,20]. Nontraumatic luxations also occur, caused by hypoplasia or aplasia of the articular disc, a hyperlax joint capsule, or an enlarged angle between the joint surface and sternum [16,19]. In most cases of acute joint dislocation, the joint can be stabilized by closed reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Indications for open reduction are recurrent posterior luxations and anterior luxations with pain, discomfort, and persistent instability [12,13,15,17]. Habitual luxations, caused by general hyperlaxity, should be distinguished from luxations caused by previous trauma and should be treated nonoperatively [16,18].…”
Section: Introductionmentioning
confidence: 99%